Social Media and Votes in the 2024 Municipal Elections: An Analysis of Electoral Performance and Interactivity on Instagram and TikTok in Brazilian Capitals - de Camargo Penteado, Claudio Luis (2025)
This article is a research of the relationship between the electoral performance of candidates in Brazilian state capitals in the 2024 municipal elections and their activity on Instagram and TikTok. In a scenario of platformization of politics, these social networks have become central to campaigns, serving for propaganda and mobilization. Based on an analysis of the posts of the two most voted candidates in each state capital, the study identified patterns of engagement, content production, and performance by type of candidacy and party. The results indicate that, although relevant, digital platforms have a limited impact on electoral success, conditioned by local factors. Incumbent candidates tend to stand out due to the logic of permanent campaigning. In addition, the study reveals the reproduction of inequalities between parties in the digital environment. Future research should explore the role of paid promotion, distinguishing its effects from organic results in electoral communication.